Pengaruh Modal, Produksi Dan Upah Tenaga Kerja Terhadap Pendapatan Studi Kasus Pada Penggilingan Padi UD Karya Jaya Periode 2017-2022 - Tri Yulianto (Akuntansi, 2024)
This research aims to determine the influence of capital, production and labor wages on UD's income. Karya Jaya Period 2017-2022. The variables in this research are Capital (X1), Internal Production (X2), Labor (X3) and Income (Y). This research uses quantitative methods using data collection techniques in the form of interviews, observation and literature study. Meanwhile, the analysis used is validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test and coefficient of determination. Sampling in this study used saturated sampling by considering all reports on capital, production and labor wages at UD. Karya Jaya for the 2017-2022 period. The results of this research used the SPSS 25.0 program using a significance level of 5% or 0.05 with result (1) partially. The results of the t test calculation on the first hypothesis obtained a calculated t value of 2.918 with a significance value of 0.006 < 0.05. These results indicate that Ha is accepted and Ho is rejected, so that there is an influence between the capital variable and income. (2) partially. The results of the t test calculation on the second hypothesis obtained a calculated t value of 1,698 with a significance value of 0.020 < 0.05. These results indicate that Ha is rejected and Ho is rejected, so that there is an influence between production variables on income. (3) partially. The results of the t test calculation on the third hypothesis obtained a calculated t value of 3,226 with a significance value of 0.003 < 0.05. These results show that Ha is rejected and Ho is rejected (3) simultaneously. The calculated F value in this study is 12,924 and the significance value of F is 0.000, which is <0.05. It can be concluded that Ha is accepted and Ho is rejected.